2013
DOI: 10.2478/pjct-2013-0057
|View full text |Cite
|
Sign up to set email alerts
|

The application of ultrafiltration for separation of glycerol solution fermented by bacteria

Abstract: A biotechnological synthesis generated a fermentation broth containing the dissociated forms of organic compounds and residual mineral salts. An effective method of selective removal of the ionic species and organic compounds from solutions comprises nanofi ltration and reverse osmosis. Ultrafi ltration (UF) was used in this work as a pre-treatment method for the preparation of feed for these processes. The UF study was carried out with a real broth, which was obtained using Citrobacter freundii bacteria for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…It indicates that microfiltration process is becoming increasingly attractive in the biotechnology industry in order to obtain a clarified filtrate from various bacterial products such as skim milk [1][2][3][4][5][6], skimmed colostrum [7], gum arabic suspension [8], cell suspension [9][10][11][12], fermentation soy sauce [13,14], and fermentation broths [15][16][17][18][19][20][21][22][23][24][25]. It has to be pointed out that with regard to complex media such as fermentation broths, microfiltration is proposed as a pre-treatment stage for the final separation by nanofiltration (NF) or reverse osmosis (RO) processes with spiral-wound modules [26].…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that microfiltration process is becoming increasingly attractive in the biotechnology industry in order to obtain a clarified filtrate from various bacterial products such as skim milk [1][2][3][4][5][6], skimmed colostrum [7], gum arabic suspension [8], cell suspension [9][10][11][12], fermentation soy sauce [13,14], and fermentation broths [15][16][17][18][19][20][21][22][23][24][25]. It has to be pointed out that with regard to complex media such as fermentation broths, microfiltration is proposed as a pre-treatment stage for the final separation by nanofiltration (NF) or reverse osmosis (RO) processes with spiral-wound modules [26].…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of culture media and fermentation, the acids produced were neutralized by the addition of sodium hydroxide. However, studies performed on Clostridium pasteurianum, C. botulinum and C. butyricum had shown that the sodium ion concentrations higher than 12 g/L inhibited cell growth 10,17 . At concentrations lower than 12 g/L, the inhibitory effect of sodium ions was not pronounced.…”
Section: 16mentioning
confidence: 99%
“…As stated before, our previous research [84,85] has revealed the effectiveness of NaOH solutions in cleaning ceramic UF membranes after treatment of glycerol postfermentation solutions with 1,3-propanediol. In light of this finding, in the present study, after completing each series of the filtration run, the fouled membrane was cleaned according to the procedure presented in Table 2.…”
Section: Methodsmentioning
confidence: 70%
“…Importantly, summarizing the literature data (Table A1) it can be indicated that NaOH has been used to clean both polymeric [25,41] and ceramic [28,42] UF membranes applied in MBR technology. Our previous investigations [84,85] highlighted the efficiency of NaOH solutions in removing foulants from ceramic UF membranes after filtration of glycerol postfermentation solutions containing 1,3-propanediol as a main product. An important point which should be noted is that the chemical cleaning process generates a waste of spent cleaning solutions which undoubtedly should be considered during the MBRs design stage.…”
Section: Introductionmentioning
confidence: 99%